(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
Essence of outplacement is considered, the stages of development of outplacement are certain in Ukraine and countries of European union and USA, advantages of the use of outplacement and stages of his realization are considered. The model of the use of outplacement is offered in realization of the effective enterprise system of social-labour relations. A value and role of outplacement are certain for three groups of subjects of social-labour relations : the state, employers and workers. The aim of work are determination of role and value of outplacement in realization of the effective enterprise system of social-labour relations. The value of аутплейсменту in realization of the effective enterprise system of social-labour relations consists in that he assists forming for the employers of social responsibility, reduction of unemployment, decline of social tension, diminishing to the risk of origin of negative consequences of liberation. The role of аутплейсменту is determined for three groups of subjects of social-labour relations. In particular, for the state: a 1) decline of unemployment rate on methodology of International organization of labour; 2) increases of level of index of global competitiveness of country; for employers: 1) book-mark of bases of socialresponsible skilled policy; 2) maintenances of business reputation which is one of important non-material assets. All participants of market are interested in reliability and honesty at the market. An enterprise with unsatisfactory reputation causes a doubt in that, whether it is needed to buy for him products and services and to co-operate with him; 3) watching of atmosphere and moods of labour collective is with the aim of counteraction to forming of negative and pessimistic moods in a collective, which assist the decline of the labour productivity; 4) protecting from publicity of commercial secret through stipulating of terms of impossibility of employment of exempt for competitors; for workers: 1) diminishing of negative moods among workers through an anxiety about them, realization of studies and retraining, exposure of new tastes and prospects of quarry height; 2) prospects of quarry height or change of lifestyle. The use of outplacement is related to the crises in an economy. The increase of part of these services in an economy certifies that although an economy is in a crisis, however responsibility increases socially for employers.